Effects of exhaust tube vortex on the in-furnace phenomena in a swirl-stabilized pulverized coal flame. (15th January 2022) - Choi, Minsung; Park, Yeseul; Deng, Kaiwen; Li, Xinzhuo; Kim, Kibeom; Sung, Yonmo; Hwang, Taegam; Choi, Gyungmin
Abstract: This paper presents an experimental investigation of the effects of the exhaust tube vortex (ETV) on pollutant emissions and carbon burnout performance. The novelty in this study is to improve understanding of combustion behavior with the ETV structure via detailed in-furnace measurements (temperature, gas-phase species concentration, carbon burnout, emissions, and etc.) in a 16-kWth coal-fired furnace. The experiment considered two different swirling flames (co- and counter-swirl) with four air staging positions. A hollow tubular structure such as the ETV structure has been created under the co-swirl condition. The values of NOx emissions are about 430 ppm, but the CO emission is lower and carbon burnout is approximately 2% higher than that of the counter-swirl unstaging condition at the furnace outlet. For the air staging conditions, the air staging position 3 ( SL 3 ) maintained the generated ETV structure stronger in the primary combustion zone. The SL 3 condition produced the lowest CO emission at about 275 ppm, and a relatively low emission of NOx showed with the highest carbon burnout performance of approximately 94.5% or more. The SL 3 condition is the most favorable condition for the synergistic effect of air staging technology on the ETV structure with a low-NOx swirl-stabilized burner. Highlights: Combining the two technologies of swirl burner and air staging produces a synergy. Combustion behavior with the ETV was evaluated by detailed in-furnace measurements. The ETV was a hollow tube structure with radius greater than 20 mm. The ETV with air staging has lower exhaust emissions and highest carbon burnout.